Morphological and molecular identificationof fungal pathogens causing gummosis disease of Citrus spp. in Indonesia - JULINDA B.D. HENUK; MEITY S. SINAGA; SRI H. HIDAYAT (Society for Indonesian Biodiversity, 2017)
Henuk JBD, Sinaga MS, Hidayat SH. 2017. Morphological and molecular identificationof fungal pathogens causing gummosis disease of Citrus spp. in Indonesia. Biodiversitas 18: 1100-1108. Gummosis is one of the most important diseases of citrus. The disease is caused by several species of Phytophthora, i.e. P. nicotianae, P. palmivora, P. citrophthora; as well as Lasiodiplodia theobromae (synonyms: Botryodiplodia theobromae and Diplodia natalensis; teleomorph Botryosphaeria rhodina). The objective of this study was to identify the isolates of fungal pathogens, i.e. Phytophthora spp. and B. theobromae and/or D. natalensis from several different areas of citrus central production in Indonesia based on their morphological and molecular characteristics. This study included two activities, i.e. (i) collection, isolation, and identification of pathogenic fungi from infected tissues, basal stem roots, and soil surface and rhizosphere; and (ii) extraction of genomic DNA and amplification of DNA fragments using PCR technique for molecular characterization. Results of morphological characterization and DNA sequence analysis revealed that gummosis was caused by Botryodiplodia theobromae Pat. (Teleomorph Botryosphaeria rhodina (Cooke) Arx.)), and P. citrophthora.